2006
DOI: 10.2135/cropsci2006.01.0060
|View full text |Cite
|
Sign up to set email alerts
|

Empirical Modeling of Genetically Modified Maize Grain Production Practices to Achieve European Union Labeling Thresholds

Abstract: An empirical approach is given for specifying coexistence requirements for genetically modified (GM) maize (Zea mays L.) production, to ensure compliance with the 0.9% labeling threshold for food and feed in the European Union. Field data were considered in which pollen-mediated gene flow (PMGF) was measured within maize receptor fields at a series of distances from source fields having a marker. An empirical model is presented that fits the observed decrease of gene flow with distance. The model was parameter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
61
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(67 citation statements)
references
References 10 publications
3
61
0
2
Order By: Relevance
“…Van de Wiel et al (2009) in the field trials in the Netherlands concluded that the grain admixtures as a consequence of pollen mediated gene transfer from GM maize were much lower: 0.080-0.084% at 25 m and 0.005-0.007% at 250 m, respectively. Our results contributed to and confirmed several previous conclusions as published by Gustafson et al (2006), Messean et al (2006), Devos et al (2007), and Sandivo et al (2008) who observed that the maize pollen grains flow and pollen mediated gene transfer decline rapidly with increased distance. These studies do also draw the attention to the impact of the isolation distances for the implementation, as well as to the negative impact on the feasibility and production cost if disproportionate measures should be implemented.…”
Section: Methodssupporting
confidence: 93%
“…Van de Wiel et al (2009) in the field trials in the Netherlands concluded that the grain admixtures as a consequence of pollen mediated gene transfer from GM maize were much lower: 0.080-0.084% at 25 m and 0.005-0.007% at 250 m, respectively. Our results contributed to and confirmed several previous conclusions as published by Gustafson et al (2006), Messean et al (2006), Devos et al (2007), and Sandivo et al (2008) who observed that the maize pollen grains flow and pollen mediated gene transfer decline rapidly with increased distance. These studies do also draw the attention to the impact of the isolation distances for the implementation, as well as to the negative impact on the feasibility and production cost if disproportionate measures should be implemented.…”
Section: Methodssupporting
confidence: 93%
“…Pollen-mediated gene flow has been quantified in detail in several crops using transgenic and marker genes including wheat (Triticum aestivum L.) (Gustafson et al, 2005;Hucl, 1996;Hucl and Matus-Cadiz, 2001;Matus-Cadiz et al, 2007), oilseed rape (B. napus) (Beckie et al, 2003;Damgaard and Kjellsson, 2005;Rieger et al, 2002;Weekes et al, 2005) and maize (Zea mays L.) (Goggi et al, 2006(Goggi et al, , 2007Gustafson et al, 2006;Weekes et al, 2007) (reviewed in Beckie andHall, 2008). Because of differences in research design and source plot size, studies are difficult to compare directly.…”
Section: Discussionmentioning
confidence: 99%
“…First, by separating the inner parts of neighboring fields, pollen barriers act as an isolation distance, in turn increasing the distance GM pollen has to travel for cross-fertilization. Second, a pollen barrier -if the GM and non-GM crops in question are the same species -introduces competing pollen and/or can serve as a physical barrier to the flow of air and, consequently, the flow of pollen [16,[27][28][29][30][31]. Accordingly, a pollen barrier reduces the extent of cross-fertilization much more effectively than an isolation perimeter of bare ground of the same width [32,33].…”
Section: Regulating Spatial Coexistence: Rigid Versus Flexible Regulamentioning
confidence: 99%